Demonstrating the impact of participative decision making, distributive justice perception and growth opportunities on favorable and unfavorable employee outcomes: Mediating effect of workplace inclusion in Indian HEIs - Aneesya Panicker; Avnish Sharma (International Journal of Business Science & Applied Management (IJBSAM), 2020)
Changing trends in the global economy have reshaped industrial relations due to transformation in the workforce composition, resulting in compulsion on companies to audit their organizational climate, HR practices, process, system, and style of managing this diversified workforce. The rationale behind this study is to assess the effect of participative decision making, distributive justice perception and growth opportunities on favorable and unfavorable employee outcomes concerning Indian HEI. Currently, India is one of the largest and fastest growing economies in the world, resulting in an increasing call to examine the pulse of workplace diversity and inclusion practices and policies, including those in India. A self-administered questionnaire was used with a non-probability sampling technique for data collection from 383 employees working in the HEIs situated in NCR, India. The proposed conceptual model was tested through correlation and regression analysis. Research results reflect significant relationships between participative decision making, distributive justice perception and growth opportunities and employee outcomes. This study provides guidelines for enhancing workplace inclusion and organizational identification on the one hand, and reducing employee turnover on the other hand, through supportive workplace inclusion measures.
Keywords: 650; workplace inclusion; participative decision making; distributive justice perception; growth opportunities; organizational identification; turnover intentions